Swedish election study 1956 - Westerståhl, Jörgen; Särlvik, Bo (University of Gothenburg, 1984)
In the first Swedish election study the respondents were interviewed twice, once before and once after the parliamentary election in September 1956. The pre-election schedule contained questions regarding interest in the election and attention to election programs in radio, and also about the respondent´s newspaper reading habits. The respondent had to point out possible retrenchment sectors and to indicate the sectors in which cuts should not be made in public expenditure, and also point out other areas for political change. Questions about trade union affiliation, union activity and opinion of the union, membership in temperance societies, free churches and church attendance were asked. The respondent had to give a prediction for the election outcome and the respondent´s political knowledge was measured through photography identification. Other questions dealt with direction and strength of party identification and political history of respondent and the respondent´s father, respondent´s interest in politics and especially the interest in the election 1956, opinion on the political parties, and degree of political interaction with family and friends. The post-election interview concentrated on the election campaign and the actual vote, when the respondent decided how to vote, if she/he changed party since last election and if this was influenced of family or friends, but there were also questions about the war risk in Europe, especially the threat of the atomic bomb, and about the Swedish defense.

Purpose:

Explain why people vote as they do and why an election ends in a particular way. Track and follow trends in the Swedish electoral democracy and make comparisons with other countries.

Valundersökningen 1956 är den första riksomfattande studien i serien undersökningar kring partival, valdeltagande och politisk opinionsbildning inom den svenska valmanskåren i samband med ett riksdagsval. I denna undersökning intervjuades respondenterna vid två tillfällen, en gång före och en gång efter andrakammarvalet i september 1956.
Förvalsintervjun innehöll frågor om intresse för valet och uppmärksamhet på valprogram i radio samt respondentens tidningsläsvanor. Respondenten fick peka ut områden där de offentliga utgifterna kan skäras ner respektive områden där de offentliga utgifterna inte får minskas, samt ange andra områden för politisk förändring.
Andra frågor berörde facklig tillhörighet och facklig aktivitet samt inställning till facket, medlemskap i nykterhetsförening, frikyrkor och kyrkobesök. Respondenten fick ge en prognos för valresultatet och den politiska kännedomen mättes genom att respondenten fick identifiera partiledarna på fotografier.
Andra frågor behandlade partiidentifikationens riktning och styrka, samt respondentens och respondentens fars politiska historik, respondentens intresse för politik och särskilt intresse för valet 1956, inställning till de politiska partierna, och graden av politisk samverkan med familj och vänner.
Eftervalsintervjun fokuserade på valkampanjen och själva omröstningen, när respondenten beslutat vilket parti man skulle rösta på, om hon/ han bytt parti sedan senaste valet och om detta påverkats av familj eller vänner, men det fanns också frågor om krigsrisken i Europa, särskilt atombombshotet, och om det svenska försvaret.

Syfte:

Förklara varför väljare röstar som de gör och varför val slutar som de gör. Spåra och följa trender i svensk valdemokrati och göra jämförelser med utvecklingen i andra länder.
Svensk valundersökning 1956
VU56
Keywords: developing countries; utvecklingsland; elections; val; housing; boende; mass media; massmedia; population migration; migration; defence; försvar; occupations; yrken; participation; deltagande; politics; politik; public sector; offentlig sektor; religion; religion; social mobility; social rörlighet; voting; röstning; political interest; politiskt intresse; political behaviour; politiskt beteende; political allegiance; politisk anhängare; political participation; politiskt deltagande; internal politics; inrikespolitik; political parties; politiska partier; political leaders; politiska ledare; trade unions; fackföreningar; political attitudes; politiska åsikter; lobbying; politisk påverkan; CORS; CORS; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Government, political systems and organisations; Regering, politiska system och organisationer; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap